Do corporate social responsibility activities enhance customer satisfaction and customer loyalty? Evidence from the Saudi banking sector - Shumookh Abdul Aziz Al-Ghamdi (Taylor & Francis Group, 2019)
This study examines the influence of corporate social responsibility activities on customer satisfaction and loyalty in the Saudi banking sector. The quantitative method was adopted by conducting a web-based survey via e-mail and social media platforms. A convenience sample of 624 banking customers in Saudi Arabia was withdrawn. Pearson’s Correlation Coefficients were generated, using statistical analyse software (SPSS 20), to test the study hypotheses. The empirical Findings of this study show that corporate social responsibility activities have a strong and positive impact on customer satisfaction and loyalty. It was also found that customer satisfaction is linked positively to customer loyalty. Findings from this paper are of importance for bank managers and directors when developing effective strategies.